Pengembangan Media Pembelajaran Interaktif Berbasis Aplikasi Android Pada Konsep Sistem Pernapasan Manusia Jenjang SMA - Pratama, Candra; Kaspul, Kaspul; Arsyad, M. (Jurnal BIOEDUIN, 2021)
Interactive learning media is one of the important learning resources components in the era of the 4.0 industrial revolution which can be accessed via smartphones or gadgets. The research objective was to produce valid interactive learning media based on Android applications. This type of research was Research and Development by using the Tessmer development model, through the preliminary and formative evaluation stages with self-evaluation and expert testing. The experts’ opinion included three validators according to expertise. The data was obtained from the research instrument in the form of a validity assessment sheet. The data collection technique used an assessment sheet. The analysis of validity data was based on very valid, valid, less valid,and invalid categories. The results showed that the Android application-based interactive learning media obtained a validity value of 94.56%, it was concluded that the validity of the developed interactive learning media based on the Android application was very valid.